The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.35800/jasm.v9i2.35523
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aquifers, humidity levels with geoelectric resistivity value, and NDW Index in the geothermal area of North Langowan

Abstract: This research was conducted to examine the condition (location, depth, and thickness) of the aquifer, to assess the humidity level using the NDW index, and to determine the relationship between aquifer conditions and the sustainability of the geothermal system using the geoelectrical method of resistivity in the North Langowan geothermal area. The comparison between rock layer resistivity data and spectral values based on geological-hydrogeological maps was carried out to determine the relationship between aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Sihotang et al (2018) classify the type of aquifer not potential because it is influenced by rock conditions in the region research dominated by claystone and siltstone. The condition of the aquifer has a classification of humidity levels including moderate wetness which indicates good continuity of the geothermal system (Wowor et al, 2021). Maemuna et al (2017) conducted research using the Schlumberger configuration found the presence of an aquifer at a depth of 7.57 -23.8 m with sand type.…”
Section: Introductionmentioning
confidence: 99%
“…Sihotang et al (2018) classify the type of aquifer not potential because it is influenced by rock conditions in the region research dominated by claystone and siltstone. The condition of the aquifer has a classification of humidity levels including moderate wetness which indicates good continuity of the geothermal system (Wowor et al, 2021). Maemuna et al (2017) conducted research using the Schlumberger configuration found the presence of an aquifer at a depth of 7.57 -23.8 m with sand type.…”
Section: Introductionmentioning
confidence: 99%